2021
DOI: 10.14202/vetworld.2021.426-436
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-typhoidal Salmonella and risk factors on poultry farms in Chitwan, Nepal

Abstract: Background and Aim: Poultry is becoming an increasingly important source of protein in the Nepalese diet. The Chitwan region of Nepal is the hub of the emerging poultry industry. Little is known about the prevalence of non-typhoidal Salmonella (NTS) on poultry farms or the role of farm management practices that may contribute to the presence of NTS on farms. The role of poultry in the transmission of Salmonella enterica to humans is also poorly defined. This descriptive study seeks establish baseline data thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(42 reference statements)
1
5
1
Order By: Relevance
“…The largely asymptomatic infected animals can spread infections across the poultry supply chain. The prevalence of Salmonella isolated from chicken feces (7.67%) in this study was similar to the previous reports; Alali et al [24] reported that Salmonella was isolated from broiler feces in organic [26]. The prevalence of Salmonella isolated from backyard chickens was 3.5% in Paraguay [27] and 12.7% from free-range chickens in China [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The largely asymptomatic infected animals can spread infections across the poultry supply chain. The prevalence of Salmonella isolated from chicken feces (7.67%) in this study was similar to the previous reports; Alali et al [24] reported that Salmonella was isolated from broiler feces in organic [26]. The prevalence of Salmonella isolated from backyard chickens was 3.5% in Paraguay [27] and 12.7% from free-range chickens in China [15].…”
Section: Discussionsupporting
confidence: 90%
“…Feeds, especially in the deep litter management systems, can become a potential source of Salmonella contamination [33,34]. Further, the prevalence of Salmonella was reported as 0.26-38.8% in the feed and 0.6-27.5% in the drinking water [4,24,26,35]. Thus, Salmonella can be transmitted back and forth among the chickens through contaminated feed and water.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that the odds of NTS infection through feed was slightly high. Other workers [ 44 ] have recently confirmed that the incidence of NTS (S. enterica) in poultry feed and feed ingredients may range from 0 to 78%, and these may serve as a source of infection on poultry farms. Pen odour increased the risk by almost two-fold, which is more an indication of the poor hygiene practices and poor litter management on the farm rather than a risk factor itself.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing good antibiotic stewardship, through collaborative education efforts among veterinarians, para-vets, and farmers could help mitigate the resistance of pathogens to antibiotics and improve the efficacy of treatment. Regulatory oversight of water quality, antibiotic sales and use, animal slaughter practices and facility hygiene, along with consumer education about food safety are critical components to control the spillover of drug-resistant strains of Salmonella from poultry to humans (Sharma et al, 2021).…”
Section: % Of Isolates Resistancementioning
confidence: 99%